Income comparison and happiness within households - Jan Salland; Ralf Dewenter (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2021)
This paper applies the German Socio-Economic Panel to analyse the effect of within household in-come comparison on individual life satisfaction. Our estimates indicate, a primary breadwinner wifedecreases spousal individual happiness by roughly nine per cent. To state the economic significance,ae70,000 increase in external, peer reference income corresponds to a similar individual happinessdecrease. The estimates suggest envy effects among couples and provide mixed evidence for genderroles to influence subjective well-being. Based on subsample estimations, our results are driven byyounger birth year quartiles, lower education and total income households, East German couples andhouseholds with greater fulltime employment share. The paper adds to within household interdepen-dence of subjective well-being and indicates negative consequences of couple income comparison forindividual happiness. Wives (barely) outearning their husbands seem to signal 'competition'.
Keywords: D10; I31; J16; 330; Life Satisfaction; Well-being; Happiness; Income Comparison; Gender Identity